A CFD-based throughflow method with an explicit body force model and an adaptive formulation for the S2 streamsurface. (February 2016) - Pacciani, Roberto; Rubechini, Filippo; Marconcini, Michele; Arnone, Andrea; Cecchi, Stefano; Daccà, Federico
The paper describes the development and validation of a novel CFD-based throughflow model. It is based on the axisymmetric Euler equations with tangential blockage and body forces and inherits its numerical scheme from state-of-the-art CFD solver (TRAF code), including real-gas capabilities. A crucial aspect of the numerical procedure is represented by an adaptive approach for the meridional flow surface, which employs a new time-dependent equation to accommodate incidence and deviation effects, and which allows the explicit calculation of the blade body force. A realistic distribution of entropy along the streamlines is proposed in order to compute dissipative forces on the basis of a distributed loss model. The throughflow code is applied to the investigation of the NASA rotor 67 transonic fan and of a four stage low-pressure steam turbine at design conditions. The performance of the method is evaluated by comparing predicted operating characteristics and spanwise distributions of flow quantities with the results of CFD, steady, viscous calculations and experimental data.